Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Find the equation of the tangent line to the curve . . . ?

I missed class - and reading the chapter isn't helping me at all at the moment.

I'm supposed to -

Find an equation of the tangent line to the curve at the given point:

y = 2x / (x + 1)^2, (0,0)

3 Answers

Relevance
  • 1 decade ago
    Favorite Answer

    The general equation for slope is given by the first derivative. I would rewrite the original using a negative exponent and use the product rule to differentiate:

    y = 2x(x+1)‾²

    y' = m = 2(x+1)‾² + (2x)(-2)(x+1)‾³(1)

    = 2(x+1)‾² - 4x(x+1)‾³

    Solve this equation where x=0 to find the slope at that point:

    m = 2(0+1)‾² - 4(0)(0+1)‾³

    = 2(1)‾² - 0

    = 2

    Since the tangent line goes through the origin (0,0) you know its y-intercept (b) is 0 and you know its slope (m) from the equation you solved:

    y = mx+b

    = 2x + 0

    y = 2x <---- that's your tangent line

  • 1 decade ago

    y = 2x /(x + 1)^2

    find y ' which is slope of tangent

    y ' = [ (x+1)^2( 2) - 2x (x+1) ] / (x + 1)^4

    y ' = 2(x + 1)[ x + 1 - x ] / (x + 1)^2

    y ' = -2 / (x + 1)

    at x = 0, y ' = -2 /1 = -2

    The eqn of tangent with slope -2 and passing through (0, 0) is

    y - 0 = -2 (x - 0)

    y = -2x

    y + 2x = 0 --------------eqn of tangent

  • Como
    Lv 7
    1 decade ago

    f ` ( x ) , by quotient rule , is given by :-

    ( x + 1 ) ² (2) - (2x) (2) ( x + 1 )

    ---------------------------------------

    ( x + 1 )^4

    ( x + 1 ) ² (2) - (4x) ( x + 1 )

    ---------------------------------------

    ( x + 1 )^4

    2 ( x + 1 ) [ ( x + 1 ) - 2x ]

    ---------------------------------------

    ( x + 1 )^4

    2 ( x + 1 ) [ 1 - x ]

    ------------------------

    ( x + 1 )^4

    2 ( 1 - x )

    ---------------

    ( x + 1 )^3

    f ` ( 0 ) = 2 = m

    y = 2x is equation of tangent line.

Still have questions? Get your answers by asking now.